Separation of iron(iii), zinc(ii) and lead(ii) from a choline chloride–ethylene glycol deep eutectic solvent by solvent extraction. Issue 55 (8th September 2020) - Spathariotis, Stylianos; Peeters, Nand; Ryder, Karl S.; Abbott, Andrew P.; Binnemans, Koen; Riaño, Sofia
Abstract : Deep eutectic solvents (DESs) were used as alternatives to the aqueous phase in solvent extraction of iron(iii ), zinc(ii ) and lead(ii ). Abstract : Deep eutectic solvents (DESs) were used as alternatives to the aqueous phase in solvent extraction of iron(iii ), zinc(ii ) and lead(ii ). The selective extraction of iron(iii ) and zinc(ii ) was studied from a feed of ethaline (1 : 2 molar ratio of choline chloride : ethylene glycol) and lactiline (1 : 2 molar ratio of choline chloride : lactic acid), with the former DES being more selective. A commercial mixture of trialkylphosphine oxides (Cyanex 923, C923) diluted in an aliphatic diluent selectively extracted iron(iii ) from a feed containing also zinc(ii ) and lead(ii ). The subsequent separation of zinc(ii ) from lead(ii ) was carried out using the basic extractant Aliquat 336 (A336). The equilibration time and the extractant concentration were optimized for both systems. Iron(iii ) and zinc(ii ) were stripped using 1.2 mol L −1 oxalic acid and 0.5 mol L −1 aqueous ammonia, respectively. An efficient solvometallurgical flowsheet is proposed for the separation and recovery of iron(iii ), lead(ii ) and zinc(ii ) from ethaline using commercial extractants. Moreover, the process was upscaled in a countercurrent mixer-settler set-up resulting in successful separation and purification.